Discourse and domination: How postmodern novels expose institutional power - Saleh, Shoeb; Shalghin, Akram H; AlAli, Rommel Mahmoud; Koka, Nisar Ahmad (Research Journal in Advanced Humanities, 2026)
Postmodern fiction is often described in aesthetic terms: irony, fragmentation, parody, and metafictional play. Yet its most durable political contribution may be its sustained attention to how institutions manufacture consent through language, narrative, and everyday routines. This article argues that many canonical postmodern novels function as laboratories for studying domination. They stage encounters between subjects and institutions (state, market, media, bureaucracy, patriarchy) and then destabilize the discursive mechanisms that make those institutions appear neutral or inevitable. Bringing together Foucauldian discourse theory, critical discourse analysis, and theories of hegemony and symbolic power, the article develops an operational framework for reading institutional domination in narrative. It then applies that framework comparatively to seven novels: Thomas Pynchon's The Crying of Lot 49 and Gravity's Rainbow, Don DeLillo's White Noise, Margaret Atwood's The Handmaid's Tale, Salman Rushdie's Midnight's Children, and J. M. Coetzee's Foe, and Toni Morrison's Beloved. Across these texts, domination is exposed not only by what institutions do but by how they speak: through bureaucratic registers, risk and expertise discourse, propaganda, archival genres, and naming practices that position subjects. Postmodern formal devices such as paranoia plots, collage, historiographic metafiction, and self-reflexive framing are shown to operate as counter-discursive strategies, training readers to perceive the politics of language and the contingency of institutional truth-claims.